Descending colon perforation due to accidental swallowing of dentures: an interesting case report - Nandu, Vipul Versi; Ghag, Geeta Sandeep; Sanjanwala, Saurabh S. (International Journal of Research in Medical Sciences, 2025)
Ingesting foreign bodies is a common occurrence, particularly in children and in a few adults (Mentally incapable, alcoholics, and people wearing dentures). Swallowed dentures are a multidisciplinary problem that concerns various fields like surgery, endoscopy, anaesthesiology, dentistry, psychiatry, neurology, thoracic surgery, and emergency medicine. Hence, swallowed dentures are considered a unique type of foreign body apart from coins, batteries, and needles. Most foreign bodies pass through the intestines without a problem. The reported complications due to ingestion of swallowed dental prosthesis include trachea-oesophageal fistula and perforation of the colon. Here, we are reporting a case of a 40-year-old male patient presenting with descending colon perforation and on surgical exploration found to have a denture protruding from the colon.